(untitled) (Environment & Health, 2019)
Objective: to determine lipid panel indices in patients with essential hypertension (EH), complicated with hemorrhagic stroke (HS), after an early recovery period; to establish a formula for calculating the dose of rosuvastatin for such patients and to assess the safety profile of its treatment in 3 months after the starting date of 1-month treatment period. Materials and methods. There were formed 2 groups of people: 107 persons (56 women and 51 men, average (M±σ) age – 54,0±9,5 years) were involved in the main group, who have undergone HS as a complication of EH 6 months and more previously; the comparison group comprised 104 persons (54 women and 50 men, middle age 53,7±8,9 years old) with EH. They were matched groups according to key indicators. All the above-mentioned people underwent blood analysis on lipid panel indices. Results. Lipid panel indices in the main and control group (M±σ) were the following ones, respectively: total cholesterol 5,998±1,326 vs. 6,027±1,103 mmol/l; triglycerides 1,422±0,775 vs. 1,975±1,136 mmol/l; low density lipoprotein 4,196±1,021 vs. 4,301±0,884 mmol/l; very low density lipoprotein 0,619±0,356 vs. 0,719±0,268 mmol/l; high density lipoprotein 1,418±0,301 vs. 1,318±0,252 mmol/l, the difference is significant (p